2023
DOI: 10.4103/ijpm.ijpm_864_21
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in oral lichen planus as assessed by the immunohistochemical evaluation of senescence marker protein-30 (Regucalcin)

Abstract: Background: Oral lichen planus is a T-cell-mediated chronic inflammatory disease affecting approximately 1% to 2% of the population, the etiology of which is currently unknown. The objectives of this study were to observe if senescence occurs in oral lichen planus, through the assessment of the immunohistochemical expression of a novel marker for senescence called Senescence marker protein-30 or regucalcin, and compare the expression to that in oral lichenoid reaction and non-specific inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have reported increased p21 CIP1/WAF1 , p16 INK4A , and p53-positive cells in patients with OLP by IHC analysis [ 23 25 ]. Other studies showed that SMP-30, a marker of senescence and anti-apoptosis, was upregulated in OLP [ 37 , 38 ]. Although these findings indicate a relationship between senescence and OLP pathogenesis, using a single senescence marker is insufficient to detect senescent cells, and applying a validated senescence gene set is considered a viable method for detecting senescence in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported increased p21 CIP1/WAF1 , p16 INK4A , and p53-positive cells in patients with OLP by IHC analysis [ 23 25 ]. Other studies showed that SMP-30, a marker of senescence and anti-apoptosis, was upregulated in OLP [ 37 , 38 ]. Although these findings indicate a relationship between senescence and OLP pathogenesis, using a single senescence marker is insufficient to detect senescent cells, and applying a validated senescence gene set is considered a viable method for detecting senescence in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%